Growth and production of Penaeus indicus in a low saline semi-intensive culture system of Kerala - Prasad, G (Indian Journal of Fisheries, 2011)
The results of a semi-intensive culture of Penaeus indicus in five brackish water ponds of low salinity (<15 ppt) are presented. The mean production was 2,557.2 kg/ha in about 115 days with an initial stocking density of 30 PL 20/ sq.m. A mean weight gain of 0.161 g/day, mean biomass increase of 2.1954 g/mVday and mean final weight of 18.356 g were realised in the present fertilised, feed applied and paddle wheel aerated culture system. The production, the weight gain per day, the biomass increase per day and the final weight at harvest were considerably higher when compared to earlier reports